Pertanggungjawaban Hukum Terhadap Perusak Lingkungan Berdasarkan Undang-Undang Nomor 32 Tahun 2009 - Aryanto, Dedy; Ardiansah; Kadaryanto, Bagio (Jurnal Panorama Hukum, 2022)
Pelalawan Regency contains a significant amount of forest land. Forest and land fires are major topics for debate. The findings of the observations suggest that forest and land fires occur often throughout the year. The goal of this research is to look at the legal responsibilities of environmental destroyers in Pelalawan Regency, as outlined in Law No. 32 of 2009 on Environmental Protection and Management. Respondents from the Head of the Service, PPNS Investigators of the Pelalawan Regency's Environmental Service, the Company, and the community participated in a qualitative sociological study. There are three types of research data: primary, secondary, and tertiary data. Observation, interviews, and library research were used to obtain data. According to the findings of the investigation, legal responsibility for environmental destroyers in Pelalawan Regency under Law No. 32 of 2009 on Environmental Protection and Management is not yet operating as planned. In Pelalawan Regency, various constraining factors have been discovered, and attempts are being undertaken to establish legal responsibility for environmental destroyers.